Gangguan Keamanan Hutan Pencurian Kayu di KPH Madiun - Bambang Hero Saharjo; Elga Tiara Putra (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Timber theft often experienced in KPH Madiun. Timber theft is the act of cutting trees or harvest or collect forest products in the forest without having any rights or permission from the authorities. This practice aims to identify the frequency of forest disturbance and loss of timber theft in KPH Madiun during the years 2011-2015, examines the characteristics of forest communities, and examine the handling of illegal logging in forest disturbance KPH Madiun. Data were collected primary and secondary data. Primary data were obtained by interviewing 30 respondents each village and field observation. While the secondary data obtained by collecting archives and document the incidence of illegal logging. The data was processed using descriptive analysis. Timber theft incidents during the last 5 years causing financial losses of Rp 3,160,154 000. The number of cases of timber theft each year has decreased significantly. Timber theft is influenced by characteristics of the community, among others, the easy accessibility of forests, extension of participation, as well as additional merencek livelihood. Weak laws and enforcement actors by the officers resulted in the theft of wood still in KPH Madiun. Strategic actions undertaken by KPH Madiun to handle timber theft through pre-emptive action (coaching), prevention (prevention) and repression (repression).Keywords: community characteristics, timber theft, the handling